Real-World ASP.NET — Building a Content Management System - Fraser, Stephen R. G. (Apress, 2013)
This book is about CMSs (I'm sure you figured that out from the front cover), but more specifically, it is a detailed programmer's look at what makes up, and how to develop, a CMS using Microsoft's new ASP.NET, C#, and the .NET Framework. Ultimately, it is a book that shows how to build a fully functional CMS at a fraction of the cost of its commercial siblings. Even if you plan to buy a much more expensive CMS, this book will explain the internal details of a CMS and should help you make the correct decision when you make your purchase.